Implementation of Marriage in the Period of Armed Conflict in Aceh - Munawar Khalil; Pagar; M. Jamil (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
This study deals with implementation of marriage in the period of armed conflict in Aceh. The marriage process during the armed conflict did not receive pre-marital guidance services nor was the registration of marriage carried out because the situation was uncertain. However, this situation is not an obstacle to the sustainability of marriage in the Acehnese society in an orderly and orderly manner. The sample of the study is North Aceh District which is the area that has the greatest influence of armed conflict between 1999 and 2005 and it also the region with the highest escalation of violence during the armed conflict, many areas in North Aceh controlled by GAM. The result shows that the implementation of the marriage which took place in the period between 1999 and 2005 was generally not administered in accordance with the prevailing laws and regulations because the Registrar of Marriage Officer did not dare to carry out their duties and functions as a public servant in checking the administration of marriage and recording it in accordance with the mandate, moreover the community is also afraid to deal with government offices.